Poor Graft and Patient Survival After Liver Transplantation in Sarcoidosis. Issue 10 (November 2020) - Thuluvath, Avesh J.; Savva, Yulia; Chen, Po-Hung
Abstract : Goals and Background: There are limited data on post-liver transplantation (LT) outcomes of patients with sarcoidosis. Study: We examined the clinical characteristics and post-LT outcomes of patients with sarcoidosis using the United Network for Organ Sharing database from 1985 to 2016 and compared them to patients (entire cohort as well as age, gender, and year of LT-matched counterparts) with primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC). For the matched design, a conditional logistic regression was used for categorical variables and marginal generalized estimating equation regression models for continuous variables. Survival functions were constructed using the Kaplan-Meier estimator. Results: A total of 206 patients with sarcoidosis, transplanted during the study period, were compared with 3933 patients with PBC and 5323 with PSC. In total, 197 patients with sarcoidosis were compared with 576 with PBC and 576 with PSC in the 1:3 matched analysis. The sarcoidosis group had a higher proportion of blacks (53.3%) and a higher prevalence of obesity and type II diabetes mellitus. The graft and patient survival for sarcoidosis patients were lower when compared with unmatched PBC and PSC patients. The results remained unchanged in the matched analysis. At 5-year, patient survival was 15% lower for the sarcoidosis group when compared with PBC and PSC. In multivariate analysis using matched data, hazard ratios (HRs) for graft (HR=1.68, 95% confidence interval=1.03-2.75, P =0.04), and patient (HR=2.01, confidence interval=1.22-3.34, P <0.01) survival were higher for sarcoidosis. Conclusions: Patients who underwent LT for sarcoidosis had a lower graft and patient survival when compared with those with PBC or PSC. That being said, 66% of patients survived 5 years after transplantation, suggesting that LT is an acceptable option in this population. Abstract : Supplemental Digital Content is available in the text.